SPE Annual Technical Conference and Exhibition 2009
DOI: 10.2118/124002-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2-ECBM/Storage Activities at the San Juan Basin's Pump Canyon Test Site

Abstract: The Southwest Regional Partnership on Carbon Sequestration (SWP) is one of seven regional partnerships sponsored by the U.S. Department of Energy (DOE) that collectively includes more than 350 organizations spanning 40 states, three Indian nations, and four Canadian provinces. The objectives are to determine the most suitable technologies, regulations and infrastructure requirements for carbon capture, storage and sequestration in different areas of the country. In Phase I of the partnership program, significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 2 publications
0
34
0
Order By: Relevance
“…Coal typically contains multicomponent gas mixtures, including methane, CO 2 , N 2 , and other heavy hydrocarbons. Strictly speaking, the primary development of CBM involves multicomponent gas desorption and it has been observed that CO 2 concentration in the produced gas increases with time over the life of wells in San Juan basin . However, most previous studies related to primary development only focus on single gas, methane, and desorption behavior and its impact on shrinkage and swelling.…”
Section: Deformation Of Coal Matrix and Fracture To Pressure/stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Coal typically contains multicomponent gas mixtures, including methane, CO 2 , N 2 , and other heavy hydrocarbons. Strictly speaking, the primary development of CBM involves multicomponent gas desorption and it has been observed that CO 2 concentration in the produced gas increases with time over the life of wells in San Juan basin . However, most previous studies related to primary development only focus on single gas, methane, and desorption behavior and its impact on shrinkage and swelling.…”
Section: Deformation Of Coal Matrix and Fracture To Pressure/stressmentioning
confidence: 99%
“…Several ECBM pilots have been conducted around the world, including the Allison Unit in San Juan basin in the USA, MOVECBM project (previously RECOPOL in Poland, Yubari site in Japan, Fenn Big Valley site in Canada, and Qinshui basin in China . Most recently, another ECBM pilot test was carried out at the Pump Canyon site in San Juan basin with the specific goal of improving understanding of the efficacy of enhanced CBM recovery processes via CO 2 injection into a pressure depleted coal seam . These pilot tests have shown that there is a significant economic and environmental benefit associated with CO 2 ‐ECBM.…”
Section: Introductionmentioning
confidence: 99%
“…While we await some post-injection monitoring results in some cases (timelapse seismic processing and analysis of two of these projects), other monitoring protocols have demonstrated containment of the CO 2 within the coal reservoirs. Using the longer-term SWP injection pilot as an example, with nearly a full year of injection, only the PFT's were detected at the offset production wells, however there was no bank of CH 4 or CO 2 detected at the production wells and the tilt meters have not indicated an increase in ground level elevation around the injection well 10 . Similarly, tracers were detected, without an increase in CO 2 or CH 4 , at the offset production wells in the Central Appalachian (SECARB) pilot test.…”
Section: Lesson #5 -No Leakage Detectedmentioning
confidence: 97%
“…Therefore, the variability in gas and water production was ascribed only to the reservoir heterogeneity. Hence, similar to Koperna et al (2009), it was assumed that wells producing at higher gas rate relate to the zones with higher cleat permeability in the vicinity and vice versa. Similarly, water production was directly related to the fracture porosity.…”
Section: Estimation Of Key Reservoir Parameters Through Geostatisticamentioning
confidence: 99%
“…Therefore, a coal seam cannot only provide site for storage of this greenhouse gas but CO 2 injection can also release additional methane from coal not recoverable by the primary pressure depletion method of producing coalbed methane (CBM), the process known as the enhanced coal bed methane (ECBM) recovery. Laboratory experiments followed by field pilots have adequately demonstrated that CO 2 sequestration in coal seams with concomitant recovery of additional methane is feasible (Reeves, 2001;Mavor et al, 2004;Pagnier et al, 2005;Wong et al, 2007;Koperna et al, 2009). However, all coal seams may not be amenable to CO 2 sequestration and ECBM.…”
Section: Introductionmentioning
confidence: 99%